Development of First-in-Class Dual Sirt2/HDAC6 Inhibitors as Molecular Tools for Dual Inhibition of Tubulin Deacetylation - Sinatra, Laura; Vogelmann, Anja; Friedrich, Florian; Tararina, Margarita A.; Neuwirt, Emilia; Colcerasa, Arianna; König, Philipp; Toy, Lara; Yesiloglu, Talha Z.; Hilscher, Sebastian; Gaitzsch, Lena; Papenkordt, Niklas; et al. (Journal of Medicinal Chemistry, 2023)
Dysregulation of both tubulin deacetylases sirtuin 2 (Sirt2) and the histone deacetylase 6 (HDAC6) has been associated with the pathogenesis of cancer and neurodegeneration, thus making these two enzymes promising targets for pharmaceutical intervention. Herein, we report the design, synthesis, and biological characterization of the first-in-class dual Sirt2/HDAC6 inhibitors as molecular tools for dual inhibition of tubulin deacetylation. Using biochemical in vitro assays and cell-based methods for target engagement, we identified Mz325 (33) as a potent and selective inhibitor of both target enzymes. Inhibition of both targets was further confirmed by X-ray crystal structures of Sirt2 and HDAC6 in complex with building blocks of 33. In ovarian cancer cells, 33 evoked enhanced effects on cell viability compared to single or combination treatment with the unconjugated Sirt2 and HDAC6 inhibitors. Thus, our dual Sirt2/HDAC6 inhibitors are important new tools to study the consequences and the therapeutic potential of dual inhibition of tubulin deacetylation.
CRIS-Team Scopus Importer:2023-11-24